Sexually transmitted diseases in women who are 50 or older: a retrospective analysis from 2000 to 2017 in a public reference service in Niterói City, Rio de Janeiro State - Maia, Mariana Cotta; Salles, Roberto de Souza; Passos, Mauro Romero Leal; Pinheiro, Vandira Maria dos Santos (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Sexually transmitted diseases (STD) are more common in young people. There are few studies on STD in the older population, particularly women. Objective: To evaluate and characterize, with epidemiological variables, the prevalence of STD in the female population over 50 years old, in a public reference service in Niterói city, Rio de Janeiro State, Brazil. Methods: The study was carried out at the STD Sector of Universidade Federal Fluminense. It was a descriptive retrospective study of quantitative character, carried out with women aged 50 or older, attended at the aforementioned teaching, research, and extension unit, from 2000 to 2017. Data collection was performed with documentary research from the records of Sexually Transmitted Diseases Sector of Universidade Federal Fluminense. A total of 6,822 records were analyzed, of which 2,363 were of women. Of these, 50 medical records of women over 50 years old. The variables used were age, education, marital status, use of condom, diagnosis, sexual and behavior characteristics (extramarital relationships and history of homosexuality), skin color, history of STD, sex education, numbers of sexual partners, family income. Results: There was a higher prevalence of human papillomavirus (HPV) infection in the form of condyloma acuminata in 48% of cases and cervical intraepithelial neoplasia (CIN) I, II, or III in 20%. Syphilis occurred in 14%; genital herpes and trichomoniasis, in 6% each; HIV, in 4%, and gonorrhea, in 2% of cases. 64% of women had no previous pathological history of STD, 6% had a previous diagnosis of syphilis, and 6%, of HPV. The predominant age group was 50 to 59 (78%), with a higher prevalence in white women (54%). Most patients (66%) reported having one fixed partner, were married (54%), and had no history of extramarital relationships (64%). In addition, 64% of patients had no degree of sex education and 56% lived on less than two minimum wages. Most patients (78%) reported not using condoms. In 50% of cases, the level of education was incomplete primary education and only 8% had concluded higher education. Conclusion: STD were more frequent in white women who did not use condoms. The most prevalent STD was HPV infection, as condyloma acuminata in pardo women. HPV infection as an cervical intraepithelial neoplasia (CIN) was the second most common STD in white and pardo women, and slightly lower in black women. Acuminated condyloma and NICs appear in all schooling groups analyzed, except in patients with a college degree and in women with higher family income. There was a predominance of STD in women without or with little sex education, and in those with low family income and education. Syphilis was observed in all age groups, predominantly in the group of good sex education, with higher family income and higher education. Syphilis and genital herpes were more prevalent in black women. Most women had a fixed sexual partnership, were married, and had no history of extramarital relationships.